PENANGGULANGAN TINDAK PIDANA PENIPUAN TERKAIT DENGAN TRANSAKSI TRANSFER DANA PADA SEKTOR PERBANKAN - Theresia Endang Ratnawati (Wacana Hukum, 2012)
Abstrak: Fraudulent acts have caused many casualties bank customers. therefore necessary lawsto protect customer responsive acting in good faith. With the issuance of Law No.8/2010, the bank actually had a legal basis to delay the transaction. Transaction delayis an act of financial services providers to not carry out transactions on their owninitiative, or upon order of the investigator, the prosecutor and the judge's order. ByLaw No. 8/2010, the bank can delay the transaction and refund the remaining funds tocustomers who become victims of fraud to protect consumers acting in good faith.Key words: transfer of funds, bank.